Overview of The Level of Anxiety in Preschool-Age Children Undergoing Hospitalization In The Children's Room of dr. H Jusuf SK Hospital - Septisari; Natalia Devi Oktarina (Program Studi S1 Keperawatan Universitas Ngudi Waluyo, 2026)
Hospitalization is a crisis situation in children, when the child is sick and treated in the hospital. Anxiety is a negative emotional state characterized by premonition and somatic tension, such as a racing heart, sweating, difficulty breathing. The ability of a person or individual to adapt varies, so that stress or anxiety can arise. Efforts from the health sector that can be developed to minimize the negative impact of child care are by approaching parents, providing a comfortable and safe environment for children, providing toys or things that are loved by children and suggesting the implementation of family-centered care. The purpose of this study was to determine the level of anxiety in preschool-aged children who were hospitalized in the Children's Ward of Dr. H. Jusuf SK Hospital. This study used quantitative descriptive research with a survey design and used a purposive sampling technique, with a sample size of 36 respondents. The instrument used was the Facial Image Scale (FIS) observation sheet. Data analysis used univariate analysis to determine the distribution of each assessment category. The results showed that the level of anxiety of respondents in the Children's Ward of Dr. H. Jusuf SK Hospital was mostly in the moderate anxiety category, namely 18 people (50.0%). For further researchers, this research can be developed by examining other influences that can affect the level of anxiety in preschool children during hospitalization that have not been studied in this study.